MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN JUMLAH SISWA DI MI PUTRA KALIJAGA - Fatonah, Kuni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2022)
Competition in the world of education in determining the number of students is very tight in today's era. Especially in private educational institutions. This can be seen from the marketing strategies carried out by various educational institutions to attract people to enter these educational institutions. This is very interesting to do research. This study aims to reveal the implementation of the marketing strategy carried out by the Putra Kalijaga MI Educational Institution. This research is a qualitative research with data collection methods through observation, in-depth interviews. The results of this study indicate that the marketing strategy in an educational institution is very important to attract new students. The marketing strategy carried out by MI Putra Kalijaga is by direct marketing which includes the use of technology, banners, and social media such as Facebook and YouTube. In addition, the strategy used is to hold outreach to kindergartens and to the community through recitations.